Green human resource management: 21st century tool for achieving sustainable development - Sapna; Anjali Gupta; Pardeep Kumar (Journal of Management and Science, 2021)
Increasing pollution from industries, scarce availability of resources in the economy, high consumption of natural resources creating urge to concern about the environment. These issues are being reported in newspapers every day. The situation is so alarming that issues are being Re discussed by environmentalists and scientists about balancing ecological imbalances. Organizations are becoming aware about the seriousness of these issues and trying to integrate environmental management into their corporate agenda in order to achieve sustainable development and competitive advantage. This paper will discuss green human resource management as a tool to achieve sustainable development on the basis of existing literature available on green Human Resource Management. An Exploratory Research design is used for the study. Papers published on green human resource management from Research gate and Google Scholar have been reviewed to achieve the aim of this study. Findings of the Study revealed that Green Human Resource Management is an effective tool for achieving Sustainable development. It will make employees and society members aware of the utilization of natural resources efficiently and economically.